2022
DOI: 10.14746/ssllt.2022.12.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating individual differences with qualitative research methods: Results of a meta-analysis of leading applied linguistics journals

Abstract: The aim of the present article is to provide a systematic review of qualitative studies in the leading journals of our field focusing on their distributional properties in the various journals as well as topic choice and selected quality control issues. In order to achieve this aim, we carried out a systematic review of research articles published in leading journals in our field, namely, Applied Linguistics, Language Learning, Language Teaching Research, Studies in Second Language Acquisition and Modern Langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Understanding learners' perceptions about the difficulty of language learning; becoming aware of the fact that there exists different aptitude and opinions among individuals about language learning and beliefs about how individuals communicate as well as knowing learners expectations in language learning; all these are essential in the process of language learning (Albert and Csizér, 2022). Furthermore, it has been suggested that successful learners evolve perceptive beliefs about their abilities and language learning processes as well as effective use of language learning strategies and the combination of all these facts are effective in the learning process (Franklin-Guy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding learners' perceptions about the difficulty of language learning; becoming aware of the fact that there exists different aptitude and opinions among individuals about language learning and beliefs about how individuals communicate as well as knowing learners expectations in language learning; all these are essential in the process of language learning (Albert and Csizér, 2022). Furthermore, it has been suggested that successful learners evolve perceptive beliefs about their abilities and language learning processes as well as effective use of language learning strategies and the combination of all these facts are effective in the learning process (Franklin-Guy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…
The subject of individual differences (IDs) has enjoyed continued popularity for more than half a century. Factors affecting language learning such as foreign language aptitude, motivation or language anxiety have been analyzed by most distinguished researchers in countless contexts and various constellations (Albert & Csizér, 2022;Resnik et al, 2022; Wen et al, 2023a). Nonetheless, few researchers have attempted to investigate IDs from the perspective of the first and the second language (L1-L2) relationships, with longitudinal studies in this regard being even less frequent.
…”
mentioning
confidence: 99%